Design of Tri-Band Filters With Improved Band Allocation - CHEN, Bo-Jiun; SHEN, Tze-Min; WU, Ruey-Beei (IEEE transactions on microwave theory and techniques, 2009)
A new design method for tri-band filters with improved band allocation is proposed. The design concept treats different band allocations with different methodologies. For the bands assigned to adjacent frequency regions, transmission zeros are introduced to split one of the single bands into two. For the bands that are assigned separately, different harmonic modes of stepped-impedance resonators are used to realize different passbands. Two design examples with different responses and band allocations are given, and were verified by experiments, as well as full-wave simulation results.